Jalur Kredit Perbankan dalam Mekanisme Transmisi Kebijakan Moneter di Indonesia - Yeniwati, Yeniwati; Riani, Novya Zulva (Fakultas Ilmu Sosial Universitas Negeri Padang, 2010)
ABSTRACT This study is to understand how the condition of the credit line in the transmission mechanism of monetary policy in Indonesia in the semi-structural analysis using the Bernanke-Blinder model VAR (Vector Autoregression), with six variable data used is the monetary policy indicator (BI rate and the interbank money market rate), Deposit (loanable funds), banking assets in the form of securities on the monetary authorities (SBI), Total Credit Banking, Economic Indicators (Output and Price). Monetary policy indicator used is the interest rate of BI rate and interest rate interbank money market monthly average, indicators of output and prices are real GDP and GDP Deflator. The study concludes that in general the existence of bank credit lines in the Indonesian economy can be believed to exist based on the results of this analysis. Kata Kunci: jalur kredit perbankan, mekanisme transmisi, kebijakan moneter.